Hydrothermally generated and highly efficient sunlight responsive SiO2 and TiO2 capped Ag2S nanocomposites for photocatalytic degradation of organic dyes. Issue 1 (February 2018) - Ayodhya, Dasari; Veerabhadram, Guttena
Graphical abstract: Highlights: Ag2 S NPs, SiO2 and TiO2 capped Ag2 S NCs were prepared by a hydrothermal method. The prepared Ag2 S NCs were characterized by various physicochemical techniques. The prepared Ag2 S NCs were exhibited an efficient photocatalytic activity. TiO2 capped Ag2 S NCs is a prominent photocatalyst in the degradation of EY and SO. The prepared Ag2 S NCs has massive photostability and reuse in several cycles. Abstract: Here, we report the synthesis of bare Ag2 S nanoparticles (NPs), SiO2 and TiO2 capped Ag2 S nanocomposites (NCs) by a simple one-pot hydrothermal method. The Ag2 S NCs, prepared by hydrothermal treatment, could be maintained and uniformly distributed on the surface of SiO2 and TiO2 precursors. The physicochemical properties of the prepared photocatalysts were characterized by XRD, SEM, TEM, TGA, FTIR, zeta potential, PL, and UV–vis DRS. The synthesized Ag2 S NPs, SiO2 and TiO2 capped Ag2 S NCs were showed strong spectral absorption capabilities in the visible regions. The diameter of prepared Ag2 S NPs, SiO2 and TiO2 capped Ag2 S NCs are observed to be in the range of 10–30 nm. Consequently, they exhibited the prominent photocatalytic behavior of the prepared Ag2 S samples for the degradation of Eosin Y (EY) and Safranin O (SO) dyes under sunlight irradiation. It shows that TiO2 capped Ag2 S NCs has exhibited an excellent photocatalytic activity in the degradation of EY (96.41%) and SO (91.38%) dyes than the bare Ag2 S NPs and SiO2 capped Ag2 S NCs. The extent of degradation was confirmed performing TOC analysis, and over 85% TOC removal was achieved. The photocatalytic degradation of EY and SO dyes was followed pseudo-first order kinetics. The prepared composite materials present properties which are highly promising for environmental clean-up applications.